I need to find all the continuous functions from $\mathbb R\rightarrow \mathbb R$ such that $f(x+y)=f(x)+f(y)+f(x)f(y)$. I know, what I assume to be, the general way to attempt these problems, but I got stuck and need a bit of help. Here is what I have so far:

Try out some cases:

Let $y=0$: $$ \begin{align} f(x)&=f(x)+f(0)+f(x)f(0) \\ 0&=f(0)+f(x)f(0) \\0 & = f(0)[1+f(x)] \end{align}$$ Observe that either $f(0)=0$ or $f(x)=-1$. So this gives me one solution, but I am having trouble finding the other solution(s). Somebody suggested to me that $f(x)=0$ is also a solution but I can't find a way to prove what they said is true. Can anyone please, without giving away the answer, give me a teeny hint? I really want to figure this out as much as I can. I've tried the case when $y=-x$ and $x=y$ but I don't feel like those cases help me towards the solution.

Thanks in advance


We have $$f(x+y) + 1 = (f(x)+1)(f(y)+1)$$ If we let $f(z) + 1$ as $g(z)$, we then have $$g(x+y) = g(x) g(y)$$ Now this is the good old Cauchy functional equation, which you should be able to solve.

Below are some relevant links:

Is there a name for function with the exponential property $f(x+y)=f(x) \cdot f(y)$?

Classifying Functions of the form $f(x+y)=f(x)f(y)$

If $f(xy)=f(x)f(y)$ then show that $f(x) = x^t$ for some t

If $f\colon \mathbb{R} \to \mathbb{R}$ is such that $f (x + y) = f (x) f (y)$ and continuous at $0$, then continuous everywhere

continuous functions on $\mathbb R$ such that $g(x+y)=g(x)g(y)$

What can we say about functions satisfying $f(a + b) = f(a)f(b) $ for all $a,b\in \mathbb{R}$?


  • $\begingroup$ Isn't the Cauchy functional equation $f(x+y)=f(x)+f(y)$? Or are a whole class of these types of functions/equations called Cauchy functional equations? $\endgroup$ – user66807 Apr 21 '13 at 18:22
  • 3
    $\begingroup$ @user66807 All are related. For instance, if you set $g(x+y) = e^{f(x+y)}$, we get $g(x+y) = g(x) g(y)$. $\endgroup$ – user17762 Apr 21 '13 at 18:23

Set $g(x)=f(x)+1$. Then $g(x+y)=g(x)g(y)\Rightarrow g(x)=g^2(\frac{x}{2}).$

Now we will prove that $g(x+y)=g(x)g(y)$ implies that $g(x)=c^x$.

First of all, $g(x)=g^2(\frac{x}{2})$ implies that $g(0)=0$ , or $g(0)=1$.

  • If $g(0)=0$ then $f(0)=-1$ and using the given relationship for $y=0, x\in \mathbb R$, we get:

$$f(x+0)=f(x)+f(0)+f(x)f(0)\Rightarrow f(x)=f(x)-1-f(x)\Rightarrow f(x)=-1,\forall x\in \mathbb R$$

  • Now, If $g(0)=1$ , we have to follow some steps in order to reach the desired conclusion:
    1. For $n\in\mathbb N$ it is easy to see that $$g(n)=g(1+\dots+1)=g(1)\times\dots\times g(1)=[g(1)]^n$$
    2. Also note that $$g(1+(-1))=g(1)g(-1)\Rightarrow g(0)=g(1)g(-1)\Rightarrow g(-1)=\dfrac{1}{g(1)}=[g(1)]^{-1}$$
    3. Now for a negative integer $-m$ we have : $$g(-m)=g(-1\dots-1)=g(-1)\times\dots\times g(-1)=[g(1)]^{-m}$$
    4. Next, prove it for $\dfrac{1}{n},n\in \mathbb N$. You have already proved that $g(2x)=g^2(x).$ If you extend this, you can easily get $g(nx)=g^n(x)$. So for $x=\frac{1}{n}$ $$g^n\left(\frac{1}{n}\right)=g(1)\Rightarrow g\left(\frac{1}{n}\right)=[g(1)]^{1/n}$$
    5. Now the big step: Prove it for rationals $\dfrac{m}{n}$ $$g\left(\frac{m}{n}\right)=g\left(\frac{1}{n}+\dots+\frac{1}{n}\right)=g\left(\frac{1}{n}\right)\times\dots\times g\left(\frac{1}{n}\right)=g\left(\frac{1}{n}\right)^m=[[g(1)]^{1/n}]^m=[g(1)]^{m/n}$$
    6. Finally, if you take a $x\in\mathbb R$, then there exists a sequence of rationals $\{q_n\}_{n=1}^\infty$ such that $q_n\xrightarrow{n\rightarrow \infty}x$ and: $$g(x)=\lim\limits_{n\rightarrow\infty}g(q_n)=\lim\limits_{n\rightarrow\infty}[g(1)]^{q_n}=[g(1)]^x$$ where we used the continuity of $g$ as well as the continuity of the exponential function.

So we reached the desired result : $$g(x)=[g(1)]^x=c^x$$ $$\Rightarrow f(x)=g(x)-1=c^x-1$$ (or $f(x)=-1$ do not forget!)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.